Review of Ctenopeuca Bernhauer, a spiny, pipevine flower-associated rove beetle from South America (Coleoptera, Staphylinidae, Aleocharinae, Oxypodini) - Barroso, Flavia B.; Eldredge, K. Taro; Caron, Edilson (Zootaxa, 2024)
Ctenopeuca Bernhauer is a genus restricted to South America, with males exhibit bimodal secondary sexual characters with alpha males having large abdominal spines and feminized spine-less beta males. In contrast to other Oxypodini genera, Ctenopeuca lacks a frontal suture on the head and has a bifid ligula. Here, we redescribe the genus and the two species, provide a diagnosis for the genus, and make remarks about its systematic position within the Oxypodini.